EULAR recommendations for the management of knee osteoarthritis: report of a task force of the Standing Committee for International Clinical Studies Including Therapeutic Trials (ESCISIT). Issue 12 (1st December 2000) - Pendleton, A; Arden, N; Dougados, M; Doherty, M; Bannwarth, B; Bijlsma, J W J; Cluzeau, F; Cooper, C; Dieppe, P A; Günther, K-P; Hauselmann, H J; Herrero-Beaumont, G; et al.
Abstract : BACKGROUND: Osteoarthritis (OA) is the most common joint disease encountered throughout Europe. A task force for the EULAR Standing Committee for Clinical Trials met in 1998 to determine the methodological and logistical approach required for the development of evidence based guidelines for treatment of knee OA. The guidelines were restricted to cover all currently available treatments for knee OA diagnosed either clinically and/or radiographically affecting any compartment of the knee. METHODS: The first stage was the selection of treatment modalities to be considered. The second stage comprised a search of the electronic databases Medline and Embase using a combination of subject headings and keywords. All European language publications in the form of systematic reviews, meta-analyses, randomised controlled trials, controlled trials, and observational studies were included. During stage three all the relevant studies were quality scored. The summary statistics for validated outcome measures, when available, were recorded and, where practical, the numbers needed to treat and the effect size for each treatment were calculated. In the fourth stage key clinical propositions were determined by expert consensus employing a Delphi approach. The final stage ranked these propositions according to the available evidence. A second set of propositions relating to a future research agenda was determined by expert consensus using a Delphi approach. RESULTS: Over 2400 English language publications and 400 non-English language publications were identified. Seven hundred and forty four studies presented outcome data of the effects of specific treatments on knee OA. Quantitative analysis of treatment effect was possible in only 61 studies. Recommendations for the management of knee OA based on currently available data and expert opinion are presented. Proposals for a future research agenda are highlighted. CONCLUSIONS: These are the first clinical guidelines on knee OA to combine an evidence based approach and a consensus approach across a wide range of treatment modalities. It is apparent that certain clinical propositions are supported by substantial research based evidence, while others are not. There is thus an urgent need for future well designed trials to consider key clinical questions.